Application development and design concepts, methodologies, tools, and applications (Engineering Science Reference, 2018)
"This book is a comprehensive reference source for the latest scholarly material on trends, techniques, and uses of various technology applications and examines the benefits and challenges of these computational developments. Highlighting a range of pertinent topics such as software design, mobile applications, and web applications"--